Genomic Engineering in Human Hematopoietic Stem Cells: Hype or Hope? - Klaver-Flores, Stefanie; Zittersteijn, Hidde A.; Canté-Barrett, Kirsten; Lankester, Arjan; Hoeben, Rob C.; Gonçalves, Manuel A. F. V.; Pike-Overzet, Karin; Staal, Frank J. T. (Frontiers in Genome Editing, 2021)
Many gene editing techniques are being developed and tested, yet, most of these are optimized for transformed cell lines, which differ from their primary cell counterparts in terms of transfectability, cell death propensity, differentiation capability and chromatin accessibility to gene editing tools. Researchers are working hard to overcome the challenges associated with gene editing of primary cells, namely, at the levels of improving the gene editing tool components, e.g. the use of modified single guide RNAs, more efficient delivery of Cas9 and RNA in the ribonucleoprotein of these cells. Despite these efforts, the low efficiency of proper gene editing in true primary cells is an obstacle that needs to be overcome in order to generate sufficiently high numbers of corrected cells for therapeutic use. In addition, many of the therapeutic candidate genes for gene editing are expressed in more mature blood cell lineages but not in the hematopoietic stem cells (HSCs), where they are tightly packed in heterochromatin, making them inaccessible to gene editing enzymes. Bringing HSCs in proliferation is sometimes seen as a solution to overcome lack of chromatin access, but the induction of proliferation in HSCs is invariably associated with loss of stemness. The documented occurrences of off-target effects and importantly on-target side effects also raise important safety issues. In conclusion, many obstacles still remain to be overcome before gene editing in HSCs can be applied clinically. Here, in a perspective way, we will discuss genetic engineering of HSCs and the challenges for developing novel therapies for monogenic diseases of the blood and immune system.